Expression of cutaneous immunity markers during infant skin maturation. Issue 4 (25th April 2018) - Kirchner, Frank; Capone, Kimberly A.; Mack, M. Catherine; Stamatas, Georgios N.
Abstract: Background/Objectives: Infant skin undergoes a maturation process during the early years of life. Little is known about the skin's innate immunity. We investigated the dynamics of innate immunity markers collected from the surface of infant skin during the first 36 months of life. Methods: A total of 117 healthy infants aged 3‐36 months participated in the study. We extracted human beta defensin‐1 and interleukin 1 alpha and its receptor antagonist using transdermal analysis patches from the skin surface of the posterior lower leg area. The extracts were analyzed using a spot enzyme‐linked immunosorbent assay. Results: Skin surface human beta defensin‐1 levels were higher early in life and decreased with infant age. The ratio of interleukin 1 alpha receptor antagonist to interleukin 1 alpha did not change significantly with age but showed a distinct difference between sexes, with female infants having higher values than male infants. Conclusion: As is the case with skin structure and functional properties, cutaneous innate immunity also appears to undergo a maturation period during infancy, with innate immunity slowly declining as adaptive immunity takes over. Sex differences in immune markers may explain sex‐dependent susceptibilities to infection.